A cross-sectional study to test equivalence of low- versus intermediate-flip angle dynamic susceptibility contrast MRI measures of relative cerebral blood volume in patients with high-grade gliomas at 1.5 Tesla field strength - Shiroishi, Mark S.; Weinert, Dane; Cen, Steven Y.; Varghese, Bino; Dondlinger, Timothy; Prah, Melissa; Mendoza, Jesse; Nazemi, Sina; Ameli, Nima; Amini, Negin; Shohas, Salman; Chen, Shannon; et al. (Frontiers in Oncology, 2023)
INTRODUCTION: Recent studies at 3T MRI have suggested that DSC-MR imaging using a 30° flip angle ("low-FA") with model-based leakage correction and no gadolinium-based contrast agent (GBCA) preload provides equivalent relative cerebral blood volume (rCBV) measurements to the reference-standard acquisition using a single-dose GBCA preload with 60° flip angle ("intermediate-FA") and model-based leakage correction. However, it remains unclear whether this holds true at 1.5T. The purpose of this study was to test this at 1.5T in human high-grade glioma (HGG). METHODS: This was a single-institution cross-sectional study of patients who had undergone 1.5T MRI for HGG. DSC-MR imaging consisted of gradient-echo echo-planar imaging with a low-FA without preload (30°/P-); this then subsequently served as a preload for the standard intermediate-FA acquisition (60°/P+). Both normalized (nrCBV) and standardized relative cerebral blood volumes (srCBV) were calculated using model-based leakage correction (C+) with IB Neuro TM software. Whole enhancing lesion mean and median nrCBV and srCBV from the low-and intermediate-flip angle methods were compared using Pearson's, Spearman's and intraclass correlation coefficients (ICC). RESULTS: Twenty-three HGG patients composing a total of 31 scans were analyzed. The Pearson and Spearman correlations and ICCs between the 30°/P-/C+ and 60°/P+/C+ acquisitions demonstrated high correlations for both mean and median nrCBV and srCBV. CONCLUSIONS: Our study provides preliminary evidence that for HGG patients at 1.5T MRI, a low FA, no preload DSC-MRI acquisition can be an appealing alternative to the reference standard higher FA acquisition that utilizes a preload for 1.5T MRI scanners.Dynamic-susceptibility contrast (DSC)-MRI-derived relative cerebral blood volume (rCBV) is the most used brain tumor perfusion imaging technique. DSC-MRI using an intermediate flip angle with singledose gadolinium-based contrast agent (GBCA) preload with model-based leakage correction is the current reference standard given its utility, accuracy and precision. However, recent computer simulations and clinical studies at 3T MRI have suggested that a simpler method using a low flip angle without the need for a GBCA preload could provide equivalent rCBV than the more complex reference standard technique in high-grade glioma (HGG) patients. This current clinical study provides further evidence that this may also hold at 1.5T in HGG patients.